Comparative Study of Quality Assurance Practices in Open Distance Learning (ODL) Universities - Tahira Bibi (International Islamic University Islamabad, 2019)
Traditional standards and measures of quality show that there are no principle standards for distance learning to achieve goals/objectives of quality assurance in Pakistan. The study was aimed to compare and gain the knowledge about current practices and measurement standards in open distance learning (ODL) at international level between the ODL universities. Threats and factors that are and will be affecting the quality of ODL and strategies that will help Pakistan to meet the high quality as benchmark for ODL were also discussed and answered through this research project with comparative perspectives. The study was conducted between August, 2016 and September, 2016. Data sets were collected from Allama Iqbal Open University (AIOU) which is the first Asian mega university of ODL and Universitas Terbuka (UT) Indonesia. Thematic analysis was employed to identify, examine and record patterns or themes within the data. The findings of the study indicated that both universities, AIOU and UT, have Quality Assurance departments namely Directorate of Quality Enhancement and Quality Assurance Unit. Directorate of Quality Enhancement is struggling for Quality Assurance with the departments and Higher Education Commission (HEC). AIOU and its departments are under the process of accreditation of the programs from various recognised bodies of HEC. Whereas University of Terbuka (UT) has accreditation of its programs from the Higher Education National Accreditation Board, certified from ISO 9001; 2008 and International Council of Distance Education. UT has centralised, well organised and well documented quality assurance unit. AIOU and UT need more efficient infrastructure, monitoring and controlling system for the e-learning and student support services at regional centers.